Genetic variability, heritability and genetic advance for growth, yield and yield related traits in maize genotypes - Roshesh Rai; Prakash Khanal; Prabin Chaudhary; Rabin Dhital (Journal of Agriculture and Applied Biology, 2021)
Evaluation of the genetic variability, heritability and genetic advance of traits is an essential task in any plant improvement program. Twenty maize genotypes were replicated twice in a randomized complete block design on a research plot of Prithu Technical College, Deukhuri Dang of Nepal from June 2017 to September 2017 to determine genetic variability, heritability, and genetic advance for different agronomic traits. Analysis of variance showed significant differences in the traits tassel length, ear height, days to fifty percent tasseling, days to fifty percent silking, kernels’ rows ear-1, kernels row-1 and grain yield. The highest GCV (31.53%) and PCV (39.20%) were recorded on grain yield. Grain yield and ear height recorded high heritability along with high genetic advance as a percent of mean (GAM). Tassel length and kernels row-1 showed high heritability integrated with moderate GAM and moderate heritability integrated with moderate GAM respectively. Further, grain yield showed a significant and positive correlation with plant height, tassel length, ear height, cob length, cob diameter, kernels’ rows ear-1, and kernels row-1. Thus the selection of ear height, tassel length and kernels row-1 is suggested as they performed better in terms of both heritability and GAM than other traits and they also recorded a significant and positive correlation with yield.